Investigation on split ring resonators based on different substrates and dimensions operating at terahertz frequency / Muhammad Zahiruddin Mohd Zahari - Mohd Zahari, Muhammad Zahiruddin
The purpose of this paper is to investigate the response of split-ring resonators (SRRs) with the operating or resonant frequency approximately at 1 THz. Different substrates and dimensions of the rings are investigated to observe the response of the SRR at the operating frequency. The main parameters concern for this project is the voltage standing wave ratio (VSWR), return loss (Sn) and the resonant frequency. The SRRs is simulated using CST Microwave Studio to obtain the response used for the investigation.